2010
DOI: 10.1016/j.laa.2010.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence relations for polynomial sequences via Riordan matrices

Abstract: We give recurrence relations for any family of generalized Appell polynomials unifying so some known recurrences of many classical sequences of polynomials. Our main tool to get our goal is the Riordan group. We use the product of Riordan matrices to interpret some relationships between different families of polynomials. Moreover using the Hadamard product of series we get a general recurrence relation for the polynomial sequences associated to the so called generalized umbral calculus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Conversely, starting from the sequences defined by (22), the infinite array (a n,k ) n,k≥0 defined by (27) is an exponential Riordan array.…”
Section: Exponential Riordan Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, starting from the sequences defined by (22), the infinite array (a n,k ) n,k≥0 defined by (27) is an exponential Riordan array.…”
Section: Exponential Riordan Arraysmentioning
confidence: 99%
“…They showed that some classical Riordan arrays have triple factorizations of the form P = P CF , where P , C, F are also Riordan arrays. We notice also that the inverse of the Stieltjes matrix represents a coefficient of the sequence polynomials [3,2,22,35]. In [34], the authors present new factorizations, and provide extensive examples of families of classical polynomials.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, after applying the evaluation map E, formula (14) gives the summation formula n k=0 r n,k f k = n! [t n ] d(t)f (h(t)) .…”
Section: Exponential Riordan Arraysmentioning
confidence: 99%
“…In [7], Luzón introduced a new notation T(f |g) to represent the Riordan arrays and gave a recurrence relation for the polynomial sequences associated to Riordan arrays. In this paper, using the production matrix of an exponential Riordan array, we give a recurrence relation for the Sheffer polynomial sequence.…”
Section: (1) a Polynomial Sequence P N (X) Is The Associated Sequencementioning
confidence: 99%